Association between nursing work environment and decision fatigue among clinical nurses: a moderated mediation analysis on the roles of job stress and resilience - Gao, ManZhi; Ou, JieFen; Cao, HuiXia; Lv, FuLu (Frontiers in Psychology, 2026)
BackgroundDecision fatigue significantly impairs nurses’ clinical judgment and threatens patient safety. Although the nursing work environment is a recognized contributor, the underlying psychological mechanisms, particularly the roles of job stress and resilience, remain inadequately explored.ObjectiveThis study aimed to test the relationship between nursing work environment, job stress and decision fatigue among clinical nurses. The study also examined the moderation role of resilience on the relationship between nursing work environment and job stress.MethodsA cross-sectional study was conducted between May 2023 and July 2023 among clinical nurses in four public hospitals in Guangdong, China. A convenience sampling method was used to collect questionnaire data from 812 clinical nurses. Data analysis was performed by SPSS 27.0, while PROCESS macro v3.5 was used to test the moderated mediation model.ResultsNursing work environment mediated by job stress had a significant positive predictive effect on decision fatigue. Resilience played a negative moderating role in the relationship between nursing work environment and job stress. For nurses with low resilience, nursing work environment had a greater impact on job stress.ConclusionThis study highlights the relationship between the nursing work environment and decision fatigue, and how job stress can be mediated and moderated by resilience.